Application of cubic spline to car body design - Nurul Ainn Ismail, 1987-, author 609230 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Harta Tanah)) - Universiti Teknologi Malaysia, 2016